PENINGKATKAN KEMAMPUAN PEMECAHAN MASALAHMATEMATIKA SISWA MELALUI PENDEKATAN MATEMATIKA REALISTIK (PMR) DI KELAS VII SMP NEGERI 4 SIPIROK - Lisna Agustina; Nur Sahara; Masdelima Azizah Sormin (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
This research was carried out in SMP N 4 Sipirok. This type of research is quasi experiment with pre test – post test control group design. The population in this study consists of the entire grade VII SMP N Sipirok, sampling is done through sampling purpose technique. Research instrument used is a test of the ability of mathematical reasoning and problem solving. Statistical hypothesis testing in this study using a t-test. An increase in problem-solving ability, the ability to understand the issues, the capabilities of the planned settlement, the ability of doing the calculations, the ability of checking back on experimental class when compared to the control class. Keywords: Problem Solving, PMR.